Bioelectronic Applications of Intrinsically Conductive Polymers - Xianglin Gao; Yilin Bao; Zhijun Chen; Jipei Lu; Tong Su; Lei Zhang; Jianyong Ouyang (Advanced Electronic Materials, 2023)
Abstract Since the discovery of conducting polyacetylene in the 1970s, intrinsically conducting polymers (ICPs) have attracted great attention because of their interesting structure, properties, and applications. Notably different from conventional conductors such as metals and doped semiconductors, ICPs have high mechanical flexibility and are light weight. In addition, their properties can be easily tuned by controlling the doping level, modifying the chemical structure, or forming composites with organic or inorganic materials. Their application in bioelectronics is particularly interesting because they have good biocompatibility and good mechanical matching with biological tissues. In this article, the methods to increase the mechanical stretchability of ICPs are first reviewed because high stretchability is often required for bioelectronic applications while pristine ICPs generally have limited stretchability. The application of ICPs as stretchable electrodes for epidermal biopotential detection and neural interfaces is discussed. Then, the employment of ICPs as the electrodes or sensing material of mechanical sensors is reviewed. They also have important application in controllable drug delivery. Last, their applications in the wearable energy harvesting and storage devices including thermoelectric generators and supercapacitors are also covered.